Validasi European System for Cardiac Operative Risk Evaluation (Euroscore) II sebagai Prediktor Lama Perawatan Intensive Care Unit (ICU) pada Pasien Operasi Bedah Jantung (Kelainan Katup dan Kongenital) di RSUP Dr. Sardjito - Febrianti, Skolastika Rani; Widyastuti, Yunita; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Background. Development quality of care, health care resources, and methods to assess the risk of cardiacsurgery are increasing in this era. Cardiac surgery is high risk procedure and require post-operative intensive care. Our objectives were to validating EuroSCORE II as ICU length of stay predictor for post cardiac surgery patient (valvular and congenital heart disease) in Dr. Sardjito General Hospital.Methods. A cohort retrospective study was conducted. Data were collected from the medical records of postoperative cardiac surgery patients in 2006-2016 at Dr. Sardjito General Hospital. EuroSCORE II values were obtained from all subjects. EuroSCORE II model was used to predict prolonged care in the ICU for >48 hours. Discriminative ability was analyzed using receiver operating characteristic (ROC) curve. Calibration were assessed with areas under the receiver operating characteristic curve (AUC) and the Hosmer– emeshow test.Results. In this study the data were obtained from 92 patients post-cardiac surgery in 2006-2016 at Dr. Sardjito General Hospital. Fifteen patients (16.3%) have prolonged ICU stay>48 hours. In this research, the predictive value is underestimate than actual value. EuroSCORE II showed good discrimination ability to predict prolonged ICU stay (AUC=0.711). However, EuroSCORE II showed poor calibration in predicting prolonged ICU stay (Hosmer-Lemeshow: p<0.05).Conclusion. EuroSCORE II showed good discrimination but poor calibration ability. EuroSCORE II can differentiate the outcome of ICU stay between ≤48 hours and >48 hours groups, but it cannot be used for patient risk stratification of prolonged ICU stay.